Adsorption of microcystin-LR on mesoporous carbons and its potential use in drinking water source. (June 2017) - Park, Jeong-Ann; Jung, Sung-Mok; Yi, In-Geol; Choi, Jae-Woo; Kim, Song-Bae; Lee, Sang-Hyup
Abstract: Microcystin-LR (MC-LR) is a common toxin derived from cyanobacterial blooms an effective, rapid and non-toxic method needs to be developed for its removal from drinking water treatment plants (DWTP). For an adsorption-based method, mesoporous carbon can be a promising supplemental adsorbent. The effect of mesoporous carbon (MC1, MC2, and MC3) properties and water quality parameters on the adsorption of MC-LR were investigated and the results were analyzed by kinetic, isotherm, thermodynamic, Derjaguin–Landau–Verwey–Overbeek (DLVO), and intraparticle diffusion models. MC1 was the most appropriate type for the removal of MC-LR with a maximum adsorption capacity of 35, 670.49 μg/g. Adsorption of MC-LR is a spontaneous reaction dominated by van der Waals interactions. Pore sizes of 8.5–14 nm enhance the pore diffusion of MC-LR from the surface to the mesopores of MC1. The adsorption capacity was not sensitive to changes in the pH (3.2–8.0) and the existence of organic matter (2–5 mg/L). Furthermore, the final concentration of MC-LR was below the WHO guideline level after a 10-min reaction with 20 mg/L of MC1 in the Nak-Dong River, a drinking water source. The MC-LR adsorption mainly competed with humic substances (500–1000 g/mole); however, they did not have a great effect on adsorption. Highlights: Mesoporous carbon adsorb MC-LR efficiently and rapidly. MC-LR adsorption is spontaneous reaction dominantly by van der Waals interaction. Pore size of 8.5–14 nm enhanced the pore diffusion of MC-LR. Adsorption was not affected by pH changes and the existence of organic matter. Mesoporous carbon remove MC-LR in drinking water source to levels below 1 μg/L.